PERSONAL DEVELOPMENT AND ACTIVITY (COMMUNICATION), THEM AS A MANAGEMENT- EDUCATIONAL- PEDAGOGICAL PROBLEM - Zhakbarova Oyazimkhon Mutalipovna (Scholars Digest Publishing, 2023)
This article describes a person as having physical, mental, political, legal, moral, ecological and aesthetic maturity.
Keywords: preformist theory, theological theory, existentialist theory, biological theory, psychoanalytic theory, biologicalized theory, motive, dialogue, psychoanalytic, psychology, biologized direction.